2013
DOI: 10.1039/c3mt00204g
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analysis of Cation Diffusion Facilitator proteins uncovers Ni2+/Co2+ transporters

Abstract: The ubiquitous Cation Diffusion Facilitator proteins (CDF) play a key role in maintaining the cellular homeostasis of essential metal ions. Previous neighbor-joining phylogenetic analysis classified CDF proteins into three substrate-defined groups: Zn(2+), Fe(2+)/Zn(2+) and Mn(2+). These studies were unable to discern substrate-defined clades for Ni(2+), Co(2+), Cd(2+) and Cu(2+) transporters, despite their existence in this family. In this study we improved the accuracy of this previous functional classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 58 publications
5
71
0
1
Order By: Relevance
“…CDF family transporters are distributed across three domains of life, and contribute to metal homeostasis by extruding divalent metal ions2425. In this study we found that the synthesis of ZitB, which shows close sequence similarity to E. coli ZitB and CzcDs from various bacteria (clade IX of the Zn transporter subfamily)24, is induced by zinc in a Zur-dependent manner in S. coelicolor .…”
Section: Discussionmentioning
confidence: 60%
“…CDF family transporters are distributed across three domains of life, and contribute to metal homeostasis by extruding divalent metal ions2425. In this study we found that the synthesis of ZitB, which shows close sequence similarity to E. coli ZitB and CzcDs from various bacteria (clade IX of the Zn transporter subfamily)24, is induced by zinc in a Zur-dependent manner in S. coelicolor .…”
Section: Discussionmentioning
confidence: 60%
“…This 227-sequence data set was subjected to multiple-sequence alignment using MUSCLE (30), which was run with maxiters ϭ 32, and the resultant alignment was used for the phylogenetic analysis. The maximum likelihood tree strategy was very similar to that recently applied to CDF proteins (31) and included 100 random seed trees in addition to a BioNJ tree to start 101 searches. Tree searching under the maximum likelihood criterion was performed with PhyML version 3.0 (32), using the LG model as the substitution matrix and ␥ correction for amongsite rate variation.…”
Section: Methodsmentioning
confidence: 99%
“…Tree searching under the maximum likelihood criterion was performed with PhyML version 3.0 (32), using the LG model as the substitution matrix and ␥ correction for amongsite rate variation. The tree searches were performed on a 13-node computer cluster as reported previously (31). The best tree ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, existing evidence indicating that the P. aeruginosa Zn 2+ -ATPase ZntA participates in the ion tolerance (M. González-Guerrero personal communication), argues against this possibility. PA1297 presents a poly-his stretch between TMS 4 and TMS 5 and belongs to the Zn 2+ transporting sub-class (Montanini et al, 2007) although recent evidence supports also a role in Co 2+ homeostasis (Cubillas et al, 2013). The absence of an Fe 2+ /Co 2+ transporting ATPase in P. aeruginosa PAO1 suggests that PA1297 product may play a role in Fe 2+ /Co 2+ homeostasis.…”
Section: Introductionmentioning
confidence: 99%